'Believing is adapting': Belief in a just world and emigrants' identification and satisfaction with the host country / 'Creer es adaptarse': Creer en un mundo justo y la identificación y satisfacción de los emigrantes con el país de acogida. Issue 2 (4th May 2017) - Leite, Ana C.; Cardoso, Sónia G.; Marques, André G.; Morais, Catarina
Abstract: In an era in which Europe is experiencing a new wave of emigration as a result of the economic crisis, it seems socially relevant to study the processes that underlie emigrants' adjustment to their new place of living. Research has thoroughly supported the assumption that believing in a just world is an adaptive mechanism that helps people to deal with uncertainty and harsh realities in life. We propose that the endorsement of such beliefs might also contribute to a positive identification with the host country. Using a sample of Portuguese emigrants ( N = 144), we demonstrate in a cross-sectional design that belief in a just world predicts a positive identification with the host country. In addition, positive levels of identification with the host country predicted higher levels of satisfaction with emigrant life. Theoretical and applied implications are discussed.